2023
DOI: 10.1007/s11764-023-01350-z
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset vascular complications of radiotherapy for primary brain tumors: a case–control and cross-sectional analysis

Abstract: Purpose Radiotherapy (RT) is a recognized risk factor for cerebrovascular (CV) disease in children and in adults with head and neck cancer. We aimed to investigate whether cerebral RT increases the risk of CV disease in adults with primary brain tumors (PBT). Methods We retrospectively identified adults with a supratentorial PBT diagnosed between 1975 and 2006 and with at least 10 years follow-up after treatment. We analyzed demographic, clinical, and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…27 While RT may induce neurovascular changes, a recently published large population-based study showed the risk of stroke-specific mortality to not be increased by RT with regards to 5-year mortality. 29 It is important to note that long-term survival in these patients may be associated with increased risk of neurovascular events 30 and late-onset vascular complications, both ischemic and hemorrhagic, 31 especially >10 years out from treatment.…”
Section: Therapeutic Deintensification: Rationale and Risksmentioning
confidence: 99%
“…27 While RT may induce neurovascular changes, a recently published large population-based study showed the risk of stroke-specific mortality to not be increased by RT with regards to 5-year mortality. 29 It is important to note that long-term survival in these patients may be associated with increased risk of neurovascular events 30 and late-onset vascular complications, both ischemic and hemorrhagic, 31 especially >10 years out from treatment.…”
Section: Therapeutic Deintensification: Rationale and Risksmentioning
confidence: 99%